SEGREGATED AND COLLABORATED EFFECT OF BALLISTIC TRAINING AND YOGIC PRACTICES ON PHYSIOLOGICAL PARAMETERS OF CRICKET PLAYERS - M.SANKAR, Dr.A.MAHABOOBJAN, Dr.V.SOWMIYA (South Eastern European Journal of Public Health, 2025)
This study was designed to investigate the segregated and collaborated effect of ballistic training and yogic practices on physiological parameters of male cricket players. To achieve the purpose of the study (N=60) sixty cricket players who participated in the inter collegiate tournament for their respective colleges, affiliated to Vinayaka Mission’s Research Foundation (Deemed to be University), Salem in the state of Tamil Nadu, India during the year 2023 – 2024 were selected as subjects. The age of the subjects ranged from 18 to 25 years. The selected players were randomly selected and assigned into four groups of fifteen subjects each (N = 15), group I underwent ballistic training (BTG), group II underwent yogic practice (YPG), group III underwent combined ballistic training and yogic practices (CBTYPG) and group IV acted as control group (CG), they were not assigned any specific training. The experimental group underwent their respective training programs for the duration of 12 weeks on alternative days, three days per week in addition to their regular programme in their curriculum design. The physiological variable such as vital capacity and breath holding time were selected as dependent variable and they were assessed by spiro meter in liters and digital stop watch in seconds. All the subjects were tested prior to and immediately after the training for the entire selected variable. The collected data were statistically analyzed using paired sample ‘t’ test and ANCOVA. If the ‘F’ ratio has significant, the Scheffe’s post hoc test was applied to know difference between the paired means. In all the cases 0.05 level of significance was fixed. It was concluded that 12 weeks combined ballistic training and yogic practice package has improve the vital capacity and breathe holding time of cricket players.